Azithromycin Prevents Pregnancy Loss: Reducing the Level of Tumor Necrosis Factor-Alpha and Raising the Level of Interleukin-10 in Rats - Ayse Er (Mediators of Inflammation)
The aim of this study was to determine the effect of azithromycin on LPS-induced pregnancy loss. Thirty-six pregnant female Wistar rats were divided into 4 equal groups as follows: control group, where 0.3 mL of normal saline solution was administered intravenously on day 10 of pregnancy; azithromycin group, where azithromycin was administered orally at 350 mg kg−1 day on days 9, 10, and 11 of pregnancy; lipopolysaccharide group, where LPS was administered intravenously via the tail vein at 160 μg kg−1 on day 10 of pregnancy; and the azithromycin + LPS group, where azithromycin was administered orally at 350 mg kg−1 day on days 9, 10, and 11 of pregnancy and LPS was administered intravenously at 160 μg kg−1 on day 10 of pregnancy. Blood samples were obtained from the tail vein on day 10 of the experiment. Pregnancy rates were determined. Tumor necrosis factor-alpha (TNF-α) and interleukin (IL-10) levels were measured by ELISA. Azithromycin prevented () LPS-induced pregnancy loss. Higher TNF-α and IL-10 levels were measured () in the LPS and azithromycin + LPS groups, respectively. In conclusion, azithromycin may be useful in infection- or endotoxemia-dependent pregnancy loss.